Supplementation strategies for forage-fed beef steers - R.D. Hunter; T.A. Nutsch; James S. Drouillard; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2000)
A comparison was made of different supplementation strategies for steer calves wintered on brome hay for 109 days. Treatments consisted of no supplement, 1.33 lb/head daily of a 30% protein range cube, a commercially available free-choice block supplement containing 40% crude protein (19% as non-protein nitrogen), and a soy-based block supplement containing soy solubles and full-fat soybeans with 40% crude protein (25% as nonprotein nitrogen). Following the backgrounding phase, steers were placed onto finishing rations and fed for an additional 152 days before being slaughtered. Gain during the growing phase was greater for all supplemented cattle than for unsupplemented controls. Cattle fed blocks or no supplement tended to compensate during the finishing phase, suggesting that differences in gastrointestinal tract fill may have impacted body weights at the end of the back grounding phase. When performance was evaluated over the entire 261-day trial, cattle fed blocks were more efficient than controls, whereas efficiencies of cattle fed range cubes were essentially equal to those of cattle that previously received no supplement. Additionally, soybean solubles and full-fat soybeans were viable alternatives to traditional ingredients for manufacturing free-choice block supplements.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Growing cattle; Forages; Blocks